2020
DOI: 10.1177/1455072520964612
|View full text |Cite
|
Sign up to set email alerts
|

Women’s views on barriers and facilitators for seeking alcohol and drug treatment in Belgium

Abstract: Aims: Although treatment barriers are different for men and women, research is dominated by males’ and practitioners’ perspectives rather than women’s voices. The purpose of this study in Belgium was to identify and obtain a better understanding of the barriers and facilitators for seeking treatment as experienced by substance (ab)using women themselves. Methods: In-depth interviews were conducted with 60 female substance users who utilise(d) outpatient and/or residential treatment services. A content analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 46 publications
0
33
0
2
Order By: Relevance
“…In their study of mental health recovery among people labelled as not criminally responsible, Aga et al (2021) found that connectedness is central to the recovery experience, including a sense of belonging that is linked to active engagement in social groups and society at large. Taking care of children has been identified as a major barrier to seeking treatment for women (because of concerns of involvement of social services and the perceived threat of child removal), as well as an important factor promoting treatment retention and recovery in mother-child programs (Neale et al, 2018;Andersson et al, 2020;Schamp et al, 2020), where reunification with children or retaining custody of children can be a strong motivation to strive for recovery.…”
Section: Introductionmentioning
confidence: 99%
“…In their study of mental health recovery among people labelled as not criminally responsible, Aga et al (2021) found that connectedness is central to the recovery experience, including a sense of belonging that is linked to active engagement in social groups and society at large. Taking care of children has been identified as a major barrier to seeking treatment for women (because of concerns of involvement of social services and the perceived threat of child removal), as well as an important factor promoting treatment retention and recovery in mother-child programs (Neale et al, 2018;Andersson et al, 2020;Schamp et al, 2020), where reunification with children or retaining custody of children can be a strong motivation to strive for recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol use is more socially acceptable ( 48 ) and risk to children from alcohol might therefore attract less stigma than drug use despite the fact that prenatal alcohol use is associated with more harm than prenatal drug use ( 49 ). Women report experiencing, or perceiving they experience, greater stigma than men due to their addiction issues especially when mothers or pregnant ( 17 , 39 , 50 , 51 ). The fear of increased stigma and concerns about the removal of children can act as a barrier to pregnant women or mothers accessing addiction and recovery services ( 51 ) which delays treatment, placing these women and their children at increased risk of harm.…”
Section: Discussionmentioning
confidence: 99%
“…Since this transfer of powers, the Flemish government puts increased emphasis on recovery-oriented and community-based services and care as an alternative to institutionalization (69,70). In recent years, the government gradually upscaled funding for substance use prevention and treatment services, including outpatient and inpatient programs for parents with SUDs and children-albeit limited- (71)(72)(73), and harm reduction initiatives (74).…”
Section: Context Of the Studymentioning
confidence: 99%